Fulminant Diabetes in a Patient with Advanced Melanoma on Nivolumab - Nora Chokr; Hafsa Farooq; Elizabeth Guadalupe (Case Reports in Oncological Medicine)
Background. Anti-PD-1 agents were approved for advanced melanoma after the landmark trial Checkmate-037. Anti-PD-1 agents can breach immunologic tolerance. Fulminant diabetes is an immune endocrinopathy that results from a violent immune attack leading to complete destruction of pancreatic beta cells in genetically predisposed people. We present a rare case of fulminant diabetes precipitated by anti-PD-1 immunotherapy. Case. A 61-year-old male with advanced melanoma presented with a three-day history of nausea, vomiting, and malaise. He was started on nivolumab and ipilimumab. After the third dose, he developed a generalized rash and was prescribed high-dose prednisone. Labs revealed potassium 9.5 mmol/L, sodium 127 mmol/L, bicarbonate <10 mmol/L, blood glucose 1211 mg/dL, anion gap >31 mmol, arterial blood pH 7.14, and beta-hydroxybutyrate 13.7 mmol/L. He was diagnosed with diabetic ketoacidosis. Hemoglobin A1C was 6.9%. C-peptide was undetectable (<0.1 ng/ml). Glutamic acid decarboxylase autoantibodies, zinc transporter 8 autoantibodies, insulin autoantibodies, islet antigen 2 autoantibodies, and islet cell antibodies were all negative. Conclusion. Anti-PD-1 immunotherapy is effective in cancers refractory to standard chemotherapy. These agents can precipitate autoimmune disorders. As the use of anti-PD-1 agents is expected to rise, physicians should be educated about the potential side effects. We recommend conducting routine blood glucose checks in patients on these agents.